Mycotoxin production in different varieties of Dactylis glomerata L. silage in response to biological and chemical additives - Alba-Mejía, Jhonny E; Domínguez-Rodríguez, Gloria; Středa, Tomáš; Středová, Hana; Lojková, Lea; Horký, Pavel; Skaličková, Sylvie; Skládanka, Jiří (PloS one, 2024)
Silage has been identified as a source of different microbial toxins, that may impair farm animal health and productivity as human health can also be compromised. In this sense, the aim of this study was to determine the impact of silage additives on the concentrations of deoxynivalenol (DON) and zearalenone (ZEN) mycotoxins and, eventually, to evaluate the hygienic quality of orchardgrass (Dactylis glomerata L.) silage based on the concentration of them compared to control silage. This study evaluated the influence of biological and chemical additives used in six different varieties of orchardgrass silage on DON and ZEN mycotoxin contents for the first time. The content of both fusariotoxins (DON and ZEN) in fresh matter and grass silage were below the threshold stipulated by the European Commission. The concentration of DON ranges from ~21.86 to 37.26 ng/kg, ~10.21 to 15 ng/kg, ~20.72 to 29.14 ng/kg; and ZEN range from ~3.42 to 7.87 ng/kg, ~3.85 to 8.62 ng/kg and ~2.15 to 5.08 ng/kg, in control, biological and chemical silages, respectively. In general, the biological additive was more efficient for preventing DON contamination, whereas the chemical additive was more efficient for preventing ZEN contamination in grass silage. In summary, the results obtained in this work demonstrate that biological and chemical additives can inhibit fungal growth and mycotoxin production on Dactylis glomerata L. silage and whose use could prevent animal and human diseases.
Keywords: Mycotoxins; mykotoxiny; Trichothecenes; Silage; Zearalenone; zvířata; siláž; Dactylis; trichotheceny; zearalenon; Animals